The British Ju-jitsu Society and the influence of Kodokan Judo on early jujutsu in the U.K. Issue 13 (1st February 2023) - Brough, David; Bradić, Slaviša; Callan, Mike; Gatling, Lance; Jones, Llyr
Abstract : In the United Kingdom (U.K.) in the late Victorian and early Edwardian eras there was an explosion in the popularity of the Japanese martial art jujutsu, with seemingly invincible Japanese exponents touring and taking on all comers in the music halls. As this early wave of popularity subsided a number of organisations were established to continue the practice of jujutsu, and other Japanese martial arts. Most notable of these was The Budokwai in London, established in 1918 by Gunji Koizumi, which from 1920 would become one of the foremost judo clubs in the West. Recent discoveries shed light on another organisation from this era called the British Ju-jitsu Society (BJS). Established in 1926, the BJS co-existed with The Budokwai and had member clubs throughout the U.K. Here, we provide an overview of the BJS, its activity, and insights into its operation and legacy.